Niesprawiedliwość epistemiczna a możliwość śledzenia trajektorii cierpienia w wywiadzie autobiograficznym. Etyczny namysł nad metodą - Neumann-Karpińska, Alicja (Kultura-Społeczeństwo-Edukacja, 2023)
In the technique of Fritz Schütze’s autobiographical interview, it is assumed that the informant faithfully recalls his experiences and tells about them as s/he experienced them. The analysis of the content and formal features of the utterance makes it possible to distinguish process structures later in the story, including the trajectory of suffering. The presented article aims to philosophically consider the ethical consequences of studying people experiencing epistemic injustice using the autobiographical narrative interview technique. Recognizing that individuals and groups subjected to treatment bearing its hallmarks do not have the appropriate means to express their experiences, and their perspective is not understood and considered in society, the author guesses that this impacts the process of reconstructing experiences during interviews. In other words, this article aims to reflect on the importance of the impact of epistemic injustice on the data obtained in interviews and to try to identify ways to minimize its impact on the research process and the conclusions formulated within it.